Microbiological Quality of Coconut Water Sold in the Grande Vitória Region, Brazil, and Phenogenotypic Antimicrobial Resistance of Associated Enterobacteria - Peterle, Valéria Modolo; Cardoso, Juliana Aliprandi Bittencourt; Ferraz, Carolina Magri; Sousa, Delcimara Ferreira de; Pereira, Natália [UNESP]; Nassar, Alessandra Figueiredo de Castro; Castro, Vanessa; Mathias, Luis Antonio [UNESP]; Cardozo, Marita Vedovelli [UNESP]; Rossi, Gabriel Augusto Marques (MDPI, 2024)
This study aimed to evaluate the microbiological quality of coconut water sold from street carts equipped with cooling coils or refrigerated at bakeries in the Grande Vitória Region, Brazil. Additionally, it assessed the phenotypic and genotypic antimicrobial resistance profiles of isolated enterobacteria. The results indicated that coconut water sold at street carts had lower microbiological quality compared to refrigerated samples, as evidenced by significantly higher counts of mesophilic microorganisms. Using MALDI-TOF, the following opportunistic pathogens were identified: Citrobacter freundii, Enterobacter bugandensis, E. kobei, E. roggenkampii, Klebsiella pneumoniae, and Kluyvera ascorbata. Three isolates—E. bugandensis, K. pneumoniae, and K. ascorbata—were classified as multidrug-resistant (MDR). Widespread resistance to β-lactams and cephalosporins was detected, and some isolates were resistant to quinolones, nitrofurans, and phosphonic acids. The gene blaCTX-M-2 was detected in C. freundii, E. bugandensis, E. kobei, and K. ascorbata. However, genes blaNDM, blaKPC, blaCMY-1, and blaCMY-2 were not detected in any isolate. The findings underscore the need to enhance good manufacturing practices in this sector to control the spread of antimicrobial resistance (AMR). To our knowledge, this is the first study documenting the presence of potentially pathogenic enterobacteria in coconut water samples and their associated phenotypic and genotypic AMR profiles.
Keywords: antibiotics; bla CTX-M-2; Citrobacter; Enterobacter; Enterobacteriaceae; ESBL; food microbiology; Klebsiella; Kluyvera